HDAC7: a promising target in cancer - Liu, Cui; Zheng, Dan; Pu, Xuan; Li, Sijun (Frontiers in Oncology, 2024)
Histones have a vital function as components of nucleosomes, which serve as the fundamental building blocks of chromatin. Histone deacetylases (HDACs), which target histones, suppress gene transcription by compacting chromatin. This implies that HDACs have a strong connection to the suppression of gene transcription. Histone deacetylation 7 (HDAC7), a member of the histone deacetylase family, may participate in multiple cellular pathophysiological processes and activate relevant signaling pathways to facilitate the progression of different tumors by exerting deacetylation. In recent years, HDAC7 has been increasingly studied in the pathogenesis of tumors. Studies that are pertinent have indicated that it has a significant impact on the growth and metastasis of tumors, the formation of the vascular microenvironment, and the emergence of resistance to drugs. Therefore, HDAC7 could potentially function as a potent predictor for tumor prognosis and a promising target for mitigating drug resistance in tumors. This review primarily concentrates on elucidating the structure and function of HDAC7, its involvement in the development of various tumors, and its interplay with relevant signaling pathways. Meanwhile, we briefly discuss the research direction and prospect of HDAC7. Vorinostat, a pan-HDAC inhibitor targeting in HDAC7 and other HDACs, has been used for the treatment of refractory cutaneous T-cell lymphoma (12). Therefore, HDAC7 has the potential to serve as a prognostic indicator and target for tumor treatment. The study of HDAC7 in tumors is growing, but there is a scarcity of comprehensive evaluations regarding the involvement of HDAC7 in tumors. This paper will review the structure, function, and role of HDAC7 in cancer.